Analisis Rasio Likuiditas dan Rasio Solvabilitas untuk Menilai Kinerja Keuangan pada PT. Alkindo Naratama Tbk di Bursa Efek Indonesia (BEI) Periode 2018-2022 - Melly Nurhasanah; Rola Manjaleni (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
These research intend to evaluate the health condition of PT Alkindo Naratama Tbk, liquidity and solvency ratios are two types of financial indicators that are significant in assessing the company's financial health. The population that is the focus of this research is the company PT Alkindo Naratama Tbk. These study takes a descriptive approach while utilizing quantitative tools in its research design. The data collection method used is by accessing annual financial reports from 2018 to 2022 published by the Indonesia Stock Exchange (IDX) as a form of documentation data. The results of data analysis obtained in this study indicate that the liquidity ratio is considered in a